Controlled deposition of palladium nanodendrites on the tips of gold nanorods and their enhanced catalytic activity. Issue 34 (17th August 2017) - Su, Gaoxing; Jiang, Huaqiao; Zhu, Hongyan; Lv, Jing-Jing; Yang, Guohai; Yan, Bing; Zhu, Jun-Jie
Abstract : Palladium nanodendrites were overgrown in a controlled manner on both ends of gold nanorods, and found to exhibit enhanced catalytic activity. Abstract : Plasmonic Au–Pd nanostructures have drawn significant attention for use in heterogeneous catalysis. In this study, palladium nanodendrite-tipped gold nanorods (PdND-T-AuNRs) were subjected to a facile fabrication under mild reaction conditions. The palladium amounts on the two tips were tunable. In the preparation of PdND-T-AuNRs, dense capped AuNRs, a low reaction temperature, and suitable stabilizing agents were identified as critical reaction parameters for controlling palladium nanodendrites deposited on both ends of AuNRs. After overgrowth with palladium nanodendrites, the longitudinal surface plasmonic resonance peaks of PdND-T-AuNRs were red-shifted from 810 nm to 980 nm. The electrocatalytic activity of PdND-T-AuNRs for ethanol oxidation was examined, which was a bit weaker than that of cuboid core–shell Au–Pd nanodendrites; however, PdND-T-AuNRs were more stable in ethanol electrooxidation. Moreover, the photocatalytic activity of PdND-T-AuNRs for Suzuki cross-coupling reactions was investigated. At room temperature, nearly 100% yield was obtained under laser irradiation. The results can further enhance our capability of fine-tuning the optical, electronic, and catalytic properties of the bimetallic Au–Pd nanostructures.